Beyond Planar Scaling:Fundamental Investigations into 3D Reconfigurable Architectures, Self-Healing Dynamics, and a New Paradigm for Semiconductor Scalin (AFOSR/IOS (SOARD) International Science) T392 - (:unkn) unknown (My University, 2026)
Inspired by previous work on 2D Adaptive Wiring Machines (AWM), which implemented a form of self-healing by continuously forming alternate connection paths, this research extends these ideas into three dimensions. In prior AFOSR-sponsored efforts, we demo